PEMBELAJARAN MENULIS TEKS DRAMA PADA SMP KELAS VIII MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE MEDIA KOMIK BERBASIS TEKNOLOGI INFORMASI - Rahayu, Dessy sri; wikanengsih, Wikanengsih; Fauziya, Diena San (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This study aims to determine the scenario and implementation of learning to write drama text for VIII grade junior high school students using the Example Non Example Model of IT-based comic media, to determine the responses of teachers and VIII grade junior high school students to learning writing drama text using The Example Non Example Model of IT-based comic media and to find out what difficulties were experienced by VIII grade junior high school students in completing the tasks of writing drama texts. This study uses a qualitative description method. The implementation of learning is in accordance with the learning scenario, but the application of the steps of the non-example model is carried out sequentially. Of the 23 students, there were 19 students who scored above the KKM standard ≥ 71 with a percentage of 82.6% categorized as "Very High". Teacher and student questionnaire sheets obtain maximum data, namely the learning of drama texts using the Example Non Example Model of IT-based comic media can provide innovative methods for students, attract student interest, and student motivation to learn. The media used for categorized students succeed in writing drama texts. Student difficulties can be seen from the average knowledge and skills. The lowest average knowledge value is 65 ≤ 100 about language rules, while the lowest average skill value is 67 ≤ 100 about structure